Investigations of radiation-induced and spontaneous chromosomal inversion formation and characteristics - Cartwright, Ian Michael, author; Kato, Takamitsu, advisor; Bailey, Susan, committee member; Bedford, Joel, committee member; Ryan, Elizabeth, committee member; Tu, Anthony, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.